Effectiveness of the Think Pair Learning Model, Experimental Method on Learning Outcomes of Class III Students in Kota Padang State Elementary Schools - Metha Lubis; Fahmiya Azlin (Science Journal Get Press, 2024)
Through collaborative problem-solving and critical thinking, students engage in the Think-Pair-Share approach, or "TPS." The objective of this approach is to improve students' critical thinking, communication, and cooperative learning skills. Students are given time to reflect alone before being broken into pairs to debate and exchange ideas. Afterwards, they report back to the class on what they discussed (Arifin, 2020). The purpose of this research is to assess the TPS learning model's efficacy in improving third-grade students' learning outcomes at the State Elementary School in Kota Padang when applied through experimental approaches. The researchers will perform this study with experimental designs that include both treated and untreated random control groups. While the TPS learning model includes experimental procedures as independent variables, students' learning outcomes may be monitored through academic examinations and performance assessments. Some students graduate but do not pass the KKM; the KKM for the IPA courses is 70; students who pass have a higher score than KKM, whilst students who do not graduate have a lower score from KKM. The average comparison test is done using the t-test; produced thitung value = 2,4029 and ttable value = 1,9971 at a significant level α = 5%. Thitung is larger than ttable, hence H0 is rejected. Improve the quality of education by obtaining broad knowledge, such as the ability to use a learning model that is appropriate for the topic. Consider the learning model Think Pair Share (TPS). According to the study, experimental approaches in learning, particularly IPA, aid to improve learners' cognitive learning results.